APLICATION OF CATFISH FLOUR ON TEXTURE AND HEDONIC PROFILES OF PEMPEK LENJER - Aminullah Aminullah; Siti Wiwi Marwiyah; Intan Kusumaningrum (AGROINTEK, 2021)
African catfish flour can be used for making pempek from premix flour. The objective was to study the effect of the catfish flour and compare tapioca and wheat flour to the texture and hedonic profiles of pempek lenjer from premix flour. The methods consisted of making catfish flour and pempek from premix flour. The treatments were catfish flours of 15%, 20%, and 25% and a comparison of tapioca and wheat flours of 1:1, 2:1, and 3:1, respectively. Analysis on catfish flour was yield and proximate characteristics, as well as analysis on pempek lenjer, were texture profiles of hardness, springiness, and stickiness, and hedonic profiles of color, aroma, taste, and springiness texture. A complete two-factor random design and Duncan’s post hoc analysis were used in the research. The results showed that catfish flour has a yield of 20%, moisture of 6,6%, ash of 1,54%, protein of 50,94%, fat of 16,75%, and carbohydrate of 24,17%. In addition, the more the catfish flour and the less the tapioca used led to the lower the hardness and the higher the springiness of pempek lenjer. However, it did not significantly affect the stickiness. The hedonic analysis showed that this pempek has a high preference value on all parameters. The texture profiles and hedonic test produced a combination of catfish flour of 20% and a comparison of tapioca and wheat flour of 2:1 as the chosen product in this research.